Education for Sustainable Development (ESD): A Journey Towards Sustainable Future - Violanda, Maria Victoria G.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Education for Sustainable Development (ESD) becomes an imperative trend among educational institutions, which requires a change in education in this modern society. Consequently, all learning institutions need to revisit its functions if it plays its vital role in transforming society by promoting social and environmental equity. This qualitative research intends to explore the faculty members’ experiences in a State College in Negros Occidental of Education for Sustainable Development (ESD). Four faculty members were purposely selected and voluntarily participated in the study. Their relevant ESD experiences were collected using semi-structured in-depth interviews, and results were analyzed using a thematic approach of Lichtman. Analysis of the data reveals exciting themes of their experiences. On becoming a greening organization member, their professional advancement and interest in the care for the environment prevailed. On the meaning of ESD, they highlighted the academe’s role in promoting sustainability. Lastly, on their ESD experiences in their classes, actions for learning through the inculcation of sustainability competencies among learners were evident. Generally, the findings suggest teachers’ significant role in promoting ESD and the importance of providing an avenue for learners to acquire the necessary knowledge, skills, and values to promote sustainability.